Preparation method of sodium alginate composite fiber membrane antibacterial dressing
By introducing carboxy quaternary ammonium salt hyperbranched polymer into the sodium alginate fiber membrane and forming an ionic crosslinking network with high crosslinking, the problem of insufficient strength and antibacterial performance of the sodium alginate fiber membrane is solved, and the toughening, hydrophilicity and antibacterial performance of the fiber membrane are improved.
Patent Information
- Application Number
- CN202410893749.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-04
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-07-04
AI Technical Summary
The sodium alginate fiber membrane has low strength and no antibacterial properties, which limits its practical application in medical supplies such as wound dressings and antibacterial dressings.
By blending sodium alginate with carboxy quaternary ammonium salt hyperbranched polymer, an ionic crosslinking network with high crosslinking degree is formed under the crosslinking action of calcium chloride, the tensile strength and water absorption of the fiber membrane are improved, and quaternary ammonium salt groups are introduced to enhance antibacterial properties.
It significantly improves the tensile strength and elongation of breaking sodium alginate fiber membrane, and enhances its water absorption and antibacterial properties, making it better practical applications in wound dressings and antibacterial dressings.
Smart Images

Figure BDA0004928337360000021 
Figure BDA0004928337360000041 
Figure BDA0004928337360000042
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sodium alginate fibers, in particular to a method for preparing a sodium alginate composite fiber film antibacterial dressing. Background Art
[0002] Sodium alginate is widely found in plants such as brown algae. It is a green, environmentally friendly, cheap and easily available natural polysaccharide polymer, which has been widely used in the food industry and the medical field. Sodium alginate can be made into fiber and fiber membrane materials by spinning, and has broad application prospects in medical supplies such as dressings and gauze. Traditional sodium alginate films and fiber membranes have low strength and do not have antibacterial properties, which is not conducive to their practical application in medical supplies such as drug-loaded dressings and wound dressings.
[0003] The patent with publication number CN116236607A discloses a high-strength and high-release micro-nanocellulose / sodium alginate dressing and its preparation method and application. With sodium alginate, hyaluronic acid, polyvinyl alcohol, calcium ions, etc. as raw materials, the obtained sodium alginate dressing has the advantages of better strength and release amount. However, the sodium alginate dressing does not have good antibacterial properties and does not show good water absorption. Improving the hydrophilicity and water absorption of the sodium alginate dressing is conducive to improving the affinity of the dressing to human skin, while improving the dressing's absorption of wound blood and exudate, and expanding the practical application of sodium alginate in wound dressings and other aspects. Summary of the invention
[0004] The invention solves the problem that the sodium alginate fiber membrane has low strength and no antibacterial property, and enables the sodium alginate fiber membrane to be better used in wound dressings, antibacterial dressings and the like.
[0005] The technical solution of the present invention is: a method for preparing a sodium alginate composite fiber membrane antibacterial dressing:
[0006] Step (1), adding sodium alginate and carboxyl quaternary ammonium salt hyperbranched polymer into distilled water, heating and stirring to mix, then cooling to room temperature to obtain spinning solution, standing and degassing, injecting into a micro-injection pump, spinning through an electrostatic spinning machine, and obtaining sodium alginate composite primary fibers.
[0007] Step (2), adding calcium chloride to ethanol, stirring and mixing to obtain a calcium chloride solution, then adding sodium alginate composite primary fiber to carry out a cross-linking reaction, pouring the solution into a clean glass plate mold for casting, drying, washing with ethanol and distilled water in turn, and drying to obtain a sodium alginate composite fiber membrane antibacterial dressing.
[0008] Furthermore, in step (1), the mass of the carboxyl quaternary ammonium salt hyperbranched polymer is 4-20% of the mass of the sodium alginate.
[0009] Furthermore, in step (1), the temperature during heating, stirring and mixing is 60-80°C; the voltage during spinning is 15-20 kV, the spinning solution flow rate is 1-2 mL / h, and the receiving distance is 10-15 cm.
[0010] Furthermore, in step (2), the mass concentration of the calcium chloride solution is (20-35) g / L.
[0011] Furthermore, in step (2), the temperature during the cross-linking reaction is 15-35° C. and the time is 24-48 hours.
[0012] Further, the preparation method of the carboxyl quaternary ammonium salt hyperbranched polymer is:
[0013] Step S1, add hydroquinone diglycidyl ether and N-methyl-2-hydroxyethylamine in a molar ratio of 1: (2.2-2.6) to tetrahydrofuran, heat to 55-65°C, react for 12-18h, concentrate the solution, and recrystallize the product in ethanol to obtain a tetrahydroxy tertiary amine monomer. The structural formula is
[0014]
[0015] Step S2, in a nitrogen atmosphere, add a tetrahydroxy tertiary amine monomer and a diacyl chloride compound in a molar ratio of 1: (2-2.1) to N,N-dimethylformamide, add triethylamine dropwise, raise the temperature to 55-75° C., react for 3-5 hours, add ethanol to dilute, filter, wash with ethanol, and dry to obtain a tertiary amine hyperbranched polymer.
[0016] Step S3, adding tertiary amino hyperbranched polymer and chloroacetic acid to N,N-dimethylformamide, heating to 90-120° C., reacting for 6-12 hours, adding ethanol to dilute after the reaction, filtering, washing with ethanol, and drying to obtain a carboxyl quaternary ammonium salt hyperbranched polymer.
[0017] Furthermore, the diacyl chloride compound is succinyl chloride, glutaryl chloride or adipoyl chloride.
[0018] Further, the mass of chloroacetic acid is 18-40% of the mass of the tertiary amine-based hyperbranched polymer.
[0019] The invention has the following technical effects: the invention carries out an epoxy addition reaction of hydroquinone diglycidyl ether with N-methyl-2-hydroxyethylamine to obtain a tetrahydroxy tertiary amine monomer containing four hydroxyl groups and two tertiary amine groups, then carries out a hyperbranched polymerization reaction with a diacyl chloride compound such as succinyl chloride, and then uses chloroacetic acid to carry out a quaternization reaction with the tertiary amine to obtain a carboxyl quaternary ammonium salt hyperbranched polymer containing a three-dimensional dendritic molecular chain.
[0020] The present invention performs electrostatic spinning by blending sodium alginate and carboxyl quaternary ammonium salt hyperbranched polymer, wherein the carboxyl quaternary ammonium salt hyperbranched polymer contains a large amount of carboxyl groups, and under the crosslinking action of calcium chloride, the carboxyl groups can be ionically crosslinked with the carboxyl groups of the sodium alginate fibers, thereby causing the carboxyl quaternary ammonium salt hyperbranched polymer to be ionically crosslinked with the sodium alginate fibers, forming a high crosslinking degree and a stable ion crosslinking network, improving the interfacial strength and compatibility of the hyperbranched polymer and the sodium alginate fibers, thereby causing the hyperbranched polymer to have a toughening effect, and improving the tensile strength and elongation at break of the fiber membrane dressing. Furthermore, the tetrahydroxy tertiary amine monomer used to prepare the hyperbranched polymer contains a rigid aromatic ring structure, thereby obtaining a hyperbranched polymer with greater strength and higher structural stability, which is beneficial to improving the tensile strength of the fiber membrane dressing.
[0021] The invention uses a tetrahydroxy tertiary amine monomer containing four hydroxyl groups and succinyl chloride to carry out hyperbranched polymerization reaction, and the obtained three-dimensional dendritic molecular chain of the hyperbranched polymer is cross-linked with sodium alginate to form a spatial porous network. The porous result is conducive to improving the water absorption rate of the fiber membrane dressing, and the hyperbranched polymer contains a large number of hydrophilic carboxyl groups and quaternary ammonium salt groups, which further improves the hydrophilicity and water absorption rate of the fiber membrane dressing. The obtained sodium alginate fiber membrane has good practical applications in wound dressings, antibacterial dressings, etc. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solution and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0023] Example 1
[0024] (1) Add 2 mmol of hydroquinone diglycidyl ether and 4.4 mmol of N-methyl-2-hydroxyethylamine to 4 mL of tetrahydrofuran, heat to 65°C, react for 12 hours, concentrate the solution, and recrystallize the product in ethanol to obtain tetrahydroxy tertiary amine monomer. The reaction formula is as follows:
[0025]
[0026] (2) In a nitrogen atmosphere, 3 mmol of tetrahydroxy tertiary amine monomer and 6 mmol of succinyl chloride were added to 30 mL of N,N-dimethylformamide, the molar ratio of the hydroxyl group of the tetrahydroxy tertiary amine monomer to the acyl chloride group of succinyl chloride being n(OH) / n(COCl)=1:1, 12 mmol of triethylamine was added dropwise, the temperature was raised to 60°C, the reaction was performed for 5 hours, ethanol was added for dilution, suction filtered, washed with ethanol, and dried to obtain a tertiary amine hyperbranched polymer. The reaction formula is as follows:
[0027]
[0028] (3) Add 5 g of tertiary amine hyperbranched polymer and 2 g of chloroacetic acid to 100 mL of N,N-dimethylformamide, heat to 90°C, react for 10 h, add ethanol to dilute, filter, wash with ethanol, and dry to obtain a carboxyl quaternary ammonium salt hyperbranched polymer. The reaction formula is as follows:
[0029]
[0030] (4) Add 20 g of sodium alginate and 0.8 g of carboxyl quaternary ammonium salt hyperbranched polymer into 250 mL of distilled water, heat to 60 °C and stir to mix, then cool to room temperature to obtain a spinning solution, let it stand for degassing and inject it into a micro-injection pump, and spin it through an electrospinning machine. The spinning voltage is 20 kV, the spinning solution flow rate is 1.5 mL / h, and the receiving distance is 10 cm to obtain sodium alginate composite primary fibers.
[0031] (5) Add calcium chloride to ethanol, stir and mix to prepare 3L of 30g / L calcium chloride solution, then add 10g of sodium alginate composite primary fiber, cross-link at 15°C for 48h, pour the solution into a clean glass plate mold, cast, dry, wash with ethanol and distilled water in turn, and dry to obtain a sodium alginate composite fiber membrane antibacterial dressing.
[0032] Example 2
[0033] (1) Add 2 mmol of hydroquinone diglycidyl ether and 5.2 mmol of N-methyl-2-hydroxyethylamine to 6 mL of tetrahydrofuran, heat to 60° C., react for 12 h, concentrate the solution, and recrystallize the product in ethanol to obtain a tetrahydroxy tertiary amine monomer.
[0034] (2) In a nitrogen atmosphere, add 3 mmol of tetrahydroxy tertiary amine monomer and 6 mmol of adipoyl chloride to 30 mL of N,N-dimethylformamide, add 12 mmol of triethylamine dropwise, raise the temperature to 75°C, react for 3 h, add ethanol to dilute, filter, wash with ethanol, and dry to obtain a tertiary amine hyperbranched polymer.
[0035] (3) Add 5 g of tertiary amine hyperbranched polymer and 1.4 g of chloroacetic acid to 80 mL of N,N-dimethylformamide, heat to 120° C., react for 6 h, add ethanol to dilute after the reaction, filter, wash with ethanol, and dry to obtain a carboxyl quaternary ammonium salt hyperbranched polymer.
[0036] (4) Add 20 g of sodium alginate and 2.8 g of carboxyl quaternary ammonium salt hyperbranched polymer into 300 mL of distilled water, heat to 80 °C and stir to mix, then cool to room temperature to obtain a spinning solution, let it stand for degassing and inject it into a micro-injection pump, and spin it through an electrospinning machine. The spinning voltage is 20 kV, the spinning solution flow rate is 2 mL / h, and the receiving distance is 10 cm to obtain sodium alginate composite primary fibers.
[0037] (5) Add calcium chloride to ethanol, stir and mix to prepare 4 L of 25 g / L calcium chloride solution, then add 10 g of sodium alginate composite primary fiber, cross-link at 35 ° C for 24 h, pour the solution into a clean glass plate mold for casting, dry, wash with ethanol and distilled water in turn, and dry to obtain a sodium alginate composite fiber membrane antibacterial dressing.
[0038] Example 3
[0039] (1) Add 2 mmol of hydroquinone diglycidyl ether and 4.8 mmol of N-methyl-2-hydroxyethylamine to 6 mL of tetrahydrofuran, heat to 55° C., react for 18 hours, concentrate the solution, and recrystallize the product in ethanol to obtain a tetrahydroxy tertiary amine monomer.
[0040] (2) In a nitrogen atmosphere, add 3 mmol of tetrahydroxy tertiary amine monomer and 6.6 mmol of glutaryl chloride to 30 mL of N,N-dimethylformamide, add 12 mmol of triethylamine dropwise, heat to 55°C, react for 5 h, add ethanol to dilute, filter, wash with ethanol, and dry to obtain a tertiary amine hyperbranched polymer.
[0041] (3) Add 5 g of tertiary amine hyperbranched polymer and 0.9 g of chloroacetic acid to 60 mL of N,N-dimethylformamide, heat to 90°C, react for 12 h, add ethanol to dilute after the reaction, filter, wash with ethanol, and dry to obtain a carboxyl quaternary ammonium salt hyperbranched polymer.
[0042] (4) Add 20 g of sodium alginate and 4 g of carboxyl quaternary ammonium salt hyperbranched polymer into 300 mL of distilled water, heat to 80 °C and stir to mix, then cool to room temperature to obtain a spinning solution, let it stand for degassing and inject it into a micro-injection pump, and spin it through an electrospinning machine. The spinning voltage is 15 kV, the spinning solution flow rate is 1 mL / h, and the receiving distance is 10 cm to obtain sodium alginate composite primary fibers.
[0043] (5) Add calcium chloride to ethanol, stir and mix to prepare 3L of 35g / L calcium chloride solution, then add 10g of sodium alginate composite primary fiber, cross-link at 25°C for 48h, pour the solution into a clean glass plate mold, cast, dry, wash with ethanol and distilled water in turn, and dry to obtain a sodium alginate composite fiber membrane antibacterial dressing.
[0044] Comparative Example 1
[0045] The difference between this comparative example and Example 1 is that when preparing the primary sodium alginate fibers, no carboxyl quaternary ammonium salt hyperbranched polymer is added.
[0046] (1) Add 20 g of sodium alginate into 250 mL of distilled water, heat to 60 °C and stir to mix, then cool to room temperature to obtain a spinning solution, let it stand for degassing, and inject it into a micro-injection pump for spinning through an electrospinning machine. The spinning voltage is 20 kV, the spinning solution flow rate is 1.5 mL / h, and the receiving distance is 10 cm to obtain sodium alginate primary fibers.
[0047] (2) Add calcium chloride to ethanol, stir and mix to prepare 3L of 30g / L calcium chloride solution, then add 10g of sodium alginate primary fiber, cross-link at 15°C for 48h, pour the solution into a clean glass plate mold, cast, dry, wash with ethanol and distilled water in turn, and dry to obtain a sodium alginate composite fiber membrane antibacterial dressing.
[0048] Comparative Example 2
[0049] The difference between this comparative example and Example 1 is that, when preparing the primary sodium alginate fibers, a tertiary amine hyperbranched polymer is used instead of a carboxyl quaternary ammonium salt hyperbranched polymer.
[0050] (1) Add 20 g of sodium alginate and 0.8 g of tertiary amine hyperbranched polymer into 250 mL of distilled water, heat to 60 °C and stir to mix, then cool to room temperature to obtain a spinning solution, let it stand for degassing and inject it into a micro-injection pump, and spin it through an electrospinning machine. The spinning voltage is 20 kV, the spinning solution flow rate is 1.5 mL / h, and the receiving distance is 10 cm to obtain sodium alginate composite primary fibers.
[0051] (2) Add calcium chloride to ethanol, stir and mix to prepare 3L of 30g / L calcium chloride solution, then add 10g of sodium alginate composite primary fiber, cross-link at 15°C for 48h, pour the solution into a clean glass plate mold, cast, dry, wash with ethanol and distilled water in turn, and dry to obtain a sodium alginate composite fiber membrane antibacterial dressing.
[0052] Comparative Example 3
[0053] The difference between this comparative example and Example 1 is that when preparing the tertiary amine polymer, N-methyldiethanolamine is used. Replace tetrahydroxy tertiary amine monomer. Control the molar ratio of the hydroxyl group of N-methyldiethanolamine to the acyl chloride group of succinyl chloride to be n(OH) / n(COCl)=1:1.
[0054] (1) In a nitrogen atmosphere, add 3 mmol N-methyldiethanolamine and 3 mmol succinyl chloride to 30 mL N,N-dimethylformamide, add 12 mmol triethylamine dropwise, heat to 60°C, react for 5 h, add ethanol to dilute, filter, wash with ethanol, and dry to obtain a tertiary amine polymer.
[0055] (2) Add 5 g of tertiary amine polymer and 2 g of chloroacetic acid to 100 mL of N,N-dimethylformamide, heat to 90°C, react for 10 h, add ethanol to dilute, filter, wash with ethanol, and dry to obtain a carboxyl quaternary ammonium salt polymer.
[0056] (3) Add 20 g of sodium alginate and 0.8 g of carboxyl quaternary ammonium salt polymer into 250 mL of distilled water, heat to 60 °C and stir to mix, then cool to room temperature to obtain a spinning solution, let it stand for degassing and inject it into a micro-injection pump, and spin it through an electrospinning machine. The spinning voltage is 20 kV, the spinning solution flow rate is 1.5 mL / h, and the receiving distance is 10 cm to obtain sodium alginate composite primary fibers.
[0057] (4) Add calcium chloride to ethanol, stir and mix to prepare 3L of 30g / L calcium chloride solution, then add 10g of sodium alginate composite primary fiber, cross-link at 15°C for 48h, pour the solution into a clean glass plate mold, cast, dry, wash with ethanol and distilled water in turn, and dry to obtain a sodium alginate composite fiber membrane antibacterial dressing.
[0058] Comparative Example 4
[0059] The difference between this comparative example and Example 1 is that when preparing the tertiary amine polymer, triethanolamine is used. Replace tetrahydroxy tertiary amine monomers. Control the molar ratio of the hydroxyl group of triethanolamine to the acyl chloride group of succinyl chloride, n(OH) / n(COCl)=1:1.
[0060] (1) In a nitrogen atmosphere, add 3 mmol of triethanolamine and 4.5 mmol of succinyl chloride to 30 mL of N,N-dimethylformamide, add 12 mmol of triethylamine dropwise, heat to 60°C, react for 5 h, add ethanol to dilute, filter, wash with ethanol, and dry to obtain a tertiary amino hyperbranched polymer.
[0061] (2) Add 5 g of tertiary amine hyperbranched polymer and 2 g of chloroacetic acid to 100 mL of N,N-dimethylformamide, heat to 90° C., react for 10 h, add ethanol to dilute after the reaction, filter, wash with ethanol, and dry to obtain a carboxyl quaternary ammonium salt hyperbranched polymer.
[0062] (3) Add 20 g of sodium alginate and 0.8 g of carboxyl quaternary ammonium salt hyperbranched polymer into 250 mL of distilled water, heat to 60 °C and stir to mix, then cool to room temperature to obtain a spinning solution, let it stand for degassing and inject it into a micro-injection pump, and spin it through an electrospinning machine. The spinning voltage is 20 kV, the spinning solution flow rate is 1.5 mL / h, and the receiving distance is 10 cm to obtain sodium alginate composite primary fibers.
[0063] (4) Add calcium chloride to ethanol, stir and mix to prepare 3L of 30g / L calcium chloride solution, then add 10g of sodium alginate composite primary fiber, cross-link at 15°C for 48h, pour the solution into a clean glass plate mold, cast, dry, wash with ethanol and distilled water in turn, and dry to obtain a sodium alginate composite fiber membrane antibacterial dressing.
[0064] The tensile strength and elongation at break of the sodium alginate composite fiber film dressing were measured using a fiber strength and elongation tester. The sample size was 100 cm × 5 cm × 1 mm, the tensile speed was 10 mm / min, and the clamp distance was 40 cm. Five samples were measured in each group and the average value was taken.
[0065] The fiber membrane dressing was made into a membrane sample of 10 cm×10 cm×2 mm, weighed, and then immersed in distilled water for 24 h. The fiber membrane dressing was taken out, the moisture on the membrane surface was absorbed with filter paper, and the sample was weighed to calculate the water absorption rate Q.
[0066] Q = (m-m0) / m0×100%. m is the mass of the fiber membrane dressing after absorbing water, and m0 is the mass of the fiber membrane dressing before absorbing water. The test results are shown in the table below.
[0067]
[0068] As can be seen from the table above, Comparative Example 1 is a common calcium chloride cross-linked sodium alginate fiber film dressing without adding carboxyl quaternary ammonium salt hyperbranched polymer. The fiber film dressing has a tensile strength of 4.21 MPa, an elongation at break of 9.13%, and a water absorption of 184.9%.
[0069] In embodiments 1, 2, and 3, when the sodium alginate fibers are cross-linked, a carboxyl quaternary ammonium salt hyperbranched polymer containing a three-dimensional dendritic molecular chain is added, which contains a large amount of carboxyl groups. Under the cross-linking action of calcium chloride, the carboxyl groups can be ionically cross-linked with the carboxyl groups of the sodium alginate fibers, thereby causing the carboxyl quaternary ammonium salt hyperbranched polymer to ionically cross-link with the sodium alginate fibers, forming a high degree of cross-linking and stable ion-crosslinked network, improving the interfacial strength and compatibility of the hyperbranched polymer and the sodium alginate fibers, thereby allowing the hyperbranched polymer to have a toughening effect, improving the tensile strength and elongation at break of the fiber membrane dressing. In addition, the tetrahydroxy tertiary amine monomer used to prepare the hyperbranched polymer contains a rigid aromatic ring structure, so that the hyperbranched polymer has a greater strength and a higher structural stability, which is conducive to improving the tensile strength of the fiber membrane dressing.
[0070] In Examples 1, 2, and 3, a tetrahydroxy tertiary amine monomer containing four hydroxyl groups is used to carry out a hyperbranched polymerization reaction with succinyl chloride, etc., and the obtained three-dimensional dendritic molecular chains of the hyperbranched polymer are cross-linked with sodium alginate to form a spatial porous network. The porous network is beneficial to improving the water absorption rate of the fiber membrane dressing, and the hyperbranched polymer contains a large number of hydrophilic carboxyl groups and quaternary ammonium salt groups, which further improves the hydrophilicity and water absorption rate of the fiber membrane dressing.
[0071] Compared with Example 1, Comparative Example 2 uses a tertiary amine hyperbranched polymer instead of a carboxyl quaternary ammonium salt hyperbranched polymer, which does not contain a carboxyl group, cannot undergo ion crosslinking with calcium chloride and sodium alginate fibers, does not form a high degree of crosslinking, stable ion crosslinked network, and has poor interfacial strength and compatibility with sodium alginate fibers, poor toughening effect, and the tensile strength and elongation at break of the fiber membrane dressing are lower than those of Example 1. In addition, the tertiary amine hyperbranched polymer does not contain hydrophilic carboxyl and quaternary ammonium salt groups, and does not crosslink with sodium alginate fibers to form a porous spatial network, resulting in a low water absorption rate of the fiber membrane dressing.
[0072] The N-methyldiethanolamine in Comparative Example 3 contains only two hydroxyl groups and cannot undergo hyperbranched polymerization reaction with succinyl chloride and the like. The obtained tertiary amine polymer and carboxyl quaternary ammonium salt polymer have a linear molecular chain structure and do not have a three-dimensional dendritic molecular chain. The toughening effect on the fiber membrane dressing is poor, and the tensile strength and elongation at break are low.
[0073] Compared with Example 1 and Comparative Example 3, the triethanolamine of Comparative Example 4 contains three hydroxyl groups, which can undergo hyperbranched polymerization with succinyl chloride and the like, and the obtained carboxyl quaternary ammonium salt polymer has a three-dimensional dendritic molecular chain, which has good toughness enhancement for the fiber membrane dressing, and the tensile strength and elongation at break are significantly higher than those of Comparative Example 1 and Comparative Example 3, but the tensile strength is significantly lower than that of Example 1, which may be because the triethanolamine does not contain a rigid aromatic ring and only contains three hydroxyl groups, while the tetrahydroxy tertiary amine monomer of Example 1 contains four hydroxyl groups, which can form a three-dimensional dendritic molecular chain with a richer branching network, resulting in the tensile strength of the fiber membrane dressing of Example 1 being significantly higher than that of Comparative Example 4. In addition, the water absorption rate of the fiber membrane dressing of Example 1 is also greater than that of Comparative Example 4, which is also related to the hyperbranched polymer of the three-dimensional dendritic molecular chain with a richer branching network, which can be cross-linked with the sodium alginate fiber to form a more spatial porous network structure, which is conducive to improving the water absorption rate.
[0074] Escherichia coli and Staphylococcus aureus were used as test bacteria. 0.5 mL of activated test bacteria suspension (10 8 cfu / mL) was evenly coated on the surface of the agar culture medium, and a fiber membrane dressing (thickness 1 mm, diameter 8 cm) sterilized by ultraviolet light was attached to the surface of the culture medium and placed in a constant temperature incubator. The culture temperature was set to 37°C and the time was set to 48 h. After culture, the diameter of the inhibition zone was measured.
[0075]
[0076] In Examples 1, 2, and 3, carboxyl quaternary ammonium salt hyperbranched polymers containing three-dimensional dendritic molecular chains are added when the sodium alginate fibers are cross-linked. The hyperbranched polymer molecular chains contain monomeric diquaternary ammonium salt antibacterial groups, which can interact with the negatively charged cell membrane surfaces of bacteria such as Escherichia coli and Staphylococcus aureus through electrostatic effects, thereby changing the permeability of the cell membranes and destroying their integrity, making it impossible for the bacteria to maintain metabolic processes and life activities, thereby exhibiting excellent bactericidal properties. The diameters of the inhibition zones of Escherichia coli and Staphylococcus aureus reach 11.7-20.5 cm and 10.5-18.2 cm, respectively.
[0077] The fiber membrane dressing of Comparative Example 1 does not contain carboxyl quaternary ammonium salt hyperbranched polymer, does not contain quaternary ammonium salt antibacterial groups, does not have antibacterial properties, and does not show an inhibition zone diameter.
[0078] The tertiary amine hyperbranched polymer of Comparative Example 2 does not contain a quaternary ammonium salt antibacterial group, has no antibacterial property, and does not show an inhibition zone diameter.
[0079] The carboxyl quaternary ammonium salt hyperbranched polymers of Comparative Examples 3 and 4 contain quaternary ammonium salt antibacterial groups, which can improve the antibacterial properties of the fiber membrane dressings, but the diameters of the inhibition zones against Escherichia coli and Staphylococcus aureus are lower than those of Example 1. It may be that N-methyldiethanolamine and triethanolamine contain only one tertiary amine group and cannot form a diquaternary ammonium salt antibacterial group, while the tetrahydroxy tertiary amine monomer contains two tertiary amine groups, which can introduce a diquaternary ammonium salt antibacterial group with better antibacterial properties into the hyperbranched polymer, thereby showing better antibacterial properties.
[0080] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.
Claims
1. A method for preparing a sodium alginate composite fiber membrane antibacterial dressing, characterized in that: The preparation method is: Step (1), adding sodium alginate and carboxyl quaternary ammonium salt hyperbranched polymer into distilled water, heating and stirring to mix, then cooling to room temperature to obtain a spinning solution, standing and degassing, injecting into a micro-injection pump, and spinning through an electrostatic spinning machine to obtain sodium alginate composite primary fibers; Step (2), adding calcium chloride to ethanol, stirring and mixing to obtain a calcium chloride solution, then adding sodium alginate composite primary fiber to carry out a cross-linking reaction, pouring the solution into a clean glass plate mold for casting, drying, washing, and drying to obtain a sodium alginate composite fiber film antibacterial dressing; The preparation method of the carboxyl quaternary ammonium salt hyperbranched polymer is: Step S1, adding hydroquinone diglycidyl ether and N-methyl-2-hydroxyethylamine in a molar ratio of 1: (2.2-2.6) to tetrahydrofuran, heating to 55-65° C., reacting for 12-18 hours, concentrating the solution, and recrystallizing the product to obtain a tetrahydroxy tertiary amine monomer; Step S2, in a nitrogen atmosphere, add a tetrahydroxy tertiary amine monomer and a diacyl chloride compound to N,N-dimethylformamide, dropwise add triethylamine, raise the temperature to 55-75° C., react for 3-5 hours, add ethanol to dilute, filter, wash, and dry to obtain a tertiary amine hyperbranched polymer; Step S3, adding a tertiary amine hyperbranched polymer and chloroacetic acid to N,N-dimethylformamide, adding ethanol to dilute after the reaction, filtering, washing, and drying to obtain a carboxyl quaternary ammonium salt hyperbranched polymer; In the step S2, the molar ratio of the tetrahydroxy tertiary amine monomer to the diacyl chloride compound is 1:(2-2.1); The diacyl chloride compound is succinyl chloride, glutaryl chloride or adipoyl chloride; The mass of the chloroacetic acid is 18-40% of the mass of the tertiary amine-based hyperbranched polymer.
2. The method for preparing the sodium alginate composite fiber membrane antibacterial dressing according to claim 1, characterized in that: In the step (1), the mass of the carboxyl quaternary ammonium salt hyperbranched polymer is 4-20% of the mass of the sodium alginate.
3. The method for preparing the sodium alginate composite fiber membrane antibacterial dressing according to claim 1, characterized in that: In the step (1), the temperature during heating, stirring and mixing is 60-80°C; the voltage during spinning is 15-20 kV, the spinning solution flow rate is 1-2 mL / h, and the receiving distance is 10-15 cm.
4. The method for preparing the sodium alginate composite fiber membrane antibacterial dressing according to claim 1, characterized in that: In the step (2), the mass concentration of the calcium chloride solution is (20-35) g / L.
5. The method for preparing the sodium alginate composite fiber membrane antibacterial dressing according to claim 1, characterized in that: In the step (2), the temperature during the cross-linking reaction is 15-35° C. and the time is 24-48 hours.
6. The method for preparing the sodium alginate composite fiber membrane antibacterial dressing according to claim 1, characterized in that: In step S3, the reaction temperature is 90-120° C. and the reaction time is 6-12 hours.
Citation Information
Patent Citations
High-strength and high-release micro-nano cellulose / sodium alginate dressing as well as preparation method and application thereof
CN116236607A
Method for preparing pure sodium alginate nano fiber membrane material
CN101230150A
Hyperbranched polylysine quaternary ammonium salt as well as preparation method and application thereof
CN117004036A